Improving the Muskingum flood routing method using a hybrid of particle swarm optimization and bat algorithm - Ehteram M.; Othman F.B.; Yaseen Z.M.; Afan H.A.; Allawi M.F.; Malek M.B.A.; Ahmed A.N.; Shahid S.; Singh V.P.; El-Shafie A. (MDPI AG, 2023)
Decision making; Disaster prevention; Floods; Routing algorithms; Water resources; Absolute deviations; Bat algorithms; Comparative analysis; Computational time; Flood routing; Muskingum models; Particle swarm optimization algorithm; Swarm algorithms; Particle swarm optimization (PSO); accuracy assessment; algorithm; comparative study; decision making; flood; flood forecasting; flood routing; numerical method; optimization; parameter estimation; water resource; United Kingdom; United States